Understanding Quality of Life for Palliative Patients With Dysphagia Using the Swallowing Quality of Life (SWAL-QOL) Questionnaire. (October 2021) - Tan, Laurence Lean Chin; Lim, Yujun; Ho, Peiyan; Lim, Lee Yen; Lim, Ying Yin; Low, James Alvin
Objective: There are few studies concerning the differences in quality-of-life (QOL) between palliative care patients with and without dysphagia to date. We aimed to compare the QOL and symptoms in palliative patients with and without dysphagia using Swallowing Quality of Life (SWAL-QOL). Methods: Eighty-one palliative patients with and without dysphagia underwent the SWAL-QOL questionnaire. A series of Mann Whitney U tests were performed between non-dysphagic and dysphagic groups for the total SWAL-QOL score and the 11 SWAL-QOL domains. Results: Dysphagia significantly impacted patients' QOL in the dysphagic group (mean, 69.5; SD 21.9) than non-dysphagic group (mean, 83.2; SD 14.8) ( P = 0.006). Significant differences were observed between both groups for the domains of burden, eating desire, eating duration, symptoms, food selection, communication and mental health. The results also showed that the dysphagic group had lower symptom score across all symptoms, suggesting higher symptom burdens. Conclusions: This study is the first to examine QOL and swallow symptoms in palliative care patients with and without dysphagia. Dysphagia causes significantly worse QOL in palliative care patients. Screening for dysphagia and managing its impact on symptoms and QOL domains is important in palliative care.